Model-Based Development and Simulation for Robotic Systems with SysML, Simulink and Simscape Profiles. (8th February 2013) - Rahman, Mohd Azizi Abdul; Mizukawa, Makoto
In system-level design, it is difficult to achieve a system verification which fulfils the requirements of various stakeholders using only descriptive system models. Descriptive system models using SysML alone are insufficient for system behaviour verifications and engineers always use different simulation tools (e.g., the Mathworks Simulink or Modelica Dymola) to analyze systems behaviour. It is a good idea to combine descriptive and simulation models. This paper presents the development of a collaborative design framework which brings SysML, Simulink, and Simscape profiles within the domain of robotics. A conceptual design method is proposed to support execution models for simulation. In brief, the descriptive SysML system-level model is interpreted into the system-level simulation models (e.g., Simulink and Simscape). We then use a plugin-based model integration technique to keep both models in sync for automatic simulation. A simulation study is performed to evaluate the system. To illustrate the design of this system, we present a simulated closed-loop system.